The Effect of Content Marketing and Online Customer Reviews on Purchasing Decisions on PVN Brand Shoe Products on The TikTok Application In Bandung City - Sihaloho, Monika; Mubarok, Dadan Abdul Aziz (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
With progress in the fashion industry, shoes are now more than just foot protection; they are an inseparable component of clothing. One of the most popular products among the Indonesian people is shoes. This study aims to determine and analyze the influence of content marketing and online customer reviews on purchase decisions regarding PVN brand shoes. Samples were taken using the Lemeshow formula. Data was collected by distributing questionnaires to 96 respondents through a Google Forms link. The data analysis method uses the multiple linear regression analysis method and path analysis by conducting classical assumption testing first. Based on the results of the multiple linear regression test, it can be concluded that the constant value is 5.375. The results of this study, namely Content Marketing and Online Customer Review, significantly affect Purchase Decisions. The F-test (Simultaneous) results of the two independent variables simultaneously affect the dependent variable